The interrelation of birth weight and regional lipid deposition: a twins study - Hng, Tien-Ming; McLean, Mark; Cheung, N. Wah; Thompson, Campbell H. (Metabolism, clinical and experimental, 2006)
This study examined the hypothesis that low birth weight is associated with changes in regional lipid deposition as well as insulin sensitivity in adult twins. Eleven adult female twin pairs were studied by magnetic resonance to determine regional adiposity. Their insulin sensitivity was assessed by the homeostasis model assessment. There were significant associations between birth weight and current homeostasis model assessment value ( r = −0.528, P = .012), abdominal visceral ( r = −0.581, P = .005), and subcutaneous fat volumes ( r = −0.638, P = .001) if the group of 22 subjects were analyzed as individuals. There were no significant associations of the intratwin pair difference in birth weight and differences between adult twins in these same variables possibly because of limited patient numbers. Reduced birth weight does confer an increased risk of abdominal adiposity as well as insulin resistance in twin populations as it does in the general population.